2019
DOI: 10.1088/1755-1315/267/5/052041
|View full text |Cite
|
Sign up to set email alerts
|

Building Information Modelling (BIM) Adoption by Quantity Surveyors: A Preliminary Survey from Malaysia

Abstract: Inefficiencies and ineffectiveness of delivering construction projects have negatively impacted the construction industry for decades. However, the emergence of BIM technology has influenced the construction process with its many benefits towards project success. Among the benefits offered by BIM are reduced project time and cost; and enhanced team collaboration and communication through the improvement of project quality and its performance. Consequently, BIM applications are claimed to provide more reliable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…This theme gives important insight into the barriers of the adoption process and mainly contributes to developing directions for future studies. While there is a rich literature on technology acceptance [55,56] and BIM adoption [57][58][59], there are a few systematic investigations of technology acceptance for lean purposes. Each theme will be discussed in Section 6.1 and Section 6.2 Figure 9 shows the frequency of themes and critical concepts discussed in three databases.…”
Section: Themes and Discussion On Recent Development On Digital Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…This theme gives important insight into the barriers of the adoption process and mainly contributes to developing directions for future studies. While there is a rich literature on technology acceptance [55,56] and BIM adoption [57][58][59], there are a few systematic investigations of technology acceptance for lean purposes. Each theme will be discussed in Section 6.1 and Section 6.2 Figure 9 shows the frequency of themes and critical concepts discussed in three databases.…”
Section: Themes and Discussion On Recent Development On Digital Toolsmentioning
confidence: 99%
“…Figure 9 also shows that other concepts received much attention, such as application development, big data, optimization, developing digital tools, and interoperability issues. Many current studies focus on the integration of these technologies for lean purposes [55,60]. These topics would most likely be continued in the following decade to address the practitioner's needs.…”
Section: Themes and Discussion On Recent Development On Digital Toolsmentioning
confidence: 99%
“…For example, studies have shown that improved decision-making process results in improved productivity of construction processes as highlighted by Liu et al (2015), Nowak et al (2016), Stransky and Dlask (2018), facilities management contributing to harmonization of real-time information (Babatunde et al (2020) and considered vital by the management and construction professionals (Sunil et al, 2017). This is also a major fulcrum upon which the BIM adoption and acceptance in the Nigerian construction industry is Ismail et al (2019), also reported that BIM adoption among the construction players has increased rapidly as a result of its numerous benefits. Furthermore, BIM has been described as a digital representation of physical and functional characteristics of a facility creating a shared knowledge resource for information about it and thus forming a reliable basis for decisions during its life cycle, from conception to demolition (Eastman et al, 2011;Suranga and Weddikkara, 2012).…”
Section: Component 1: Construction-related Drivermentioning
confidence: 97%
“…Studies have shown that BIM estimating greatly improves the accuracy of estimates, and visualize realworld conditions through a virtual three-dimensional construction of the building (Sylvester and Dietrich, 2010). The cost estimating process regardless of methods adopted is necessary for estimates to be reliable and accurate (Ismail et al, 2019). The inherent ability of BIM models to be used for easy estimating has also been identified among the major reasons for BIM usage projects by professionals and clients (Madugu et al, 2016).…”
Section: Component 1: Construction-related Drivermentioning
confidence: 99%
“…Olatunji et al (2010) described that, BIM is a major challenge to the services conventionally provided by quantity surveyors and other construction disciplines as the adoption of BIM may redefine traditional professional boundaries in construction. A recent study by (Ismail, Adnan, & Bakhary, 2019) found that majority of quantity surveyors were aware of BIM usage, and have moderate knowledge of BIM but they did not use it in their practice.…”
Section: Problem Statementmentioning
confidence: 99%